Dopamine receptor genes and evolutionary differentiation in the domestication of fighting cocks and long-crowing chickens. - Tomoyoshi Komiyama; Hisakazu Iwama; Naoki Osada; Yoji Nakamura; Hiroyuki Kobayashi; Yoshio Tateno; Takashi Gojobori (PLoS ONE, 2014)
The chicken domestication process represents a typical model of artificial selection, and gives significant insight into the general understanding of the influence of artificial selection on recognizable phenotypes. Two Japanese domesticated chicken varieties, the fighting cock (Shamo) and the long-crowing chicken (Naganakidori), have been selectively bred for dramatically different phenotypes. The former has been selected exclusively for aggressiveness and the latter for long crowing with an obedient sitting posture. To understand the particular mechanism behind these genetic changes during domestication, we investigated the degree of genetic differentiation in the aforementioned chickens, focusing on dopamine receptor D2, D3, and D4 genes. We studied other ornamental chickens such as Chabo chickens as a reference for comparison. When genetic differentiation was measured by an index of nucleotide differentiation (NST) newly devised in this study, we found that the NST value of DRD4 for Shamo (0.072) was distinctively larger than those of the other genes among the three populations, suggesting that aggressiveness has been selected for in Shamo by collecting a variety of single nucleotide polymorphisms. In addition, we found that in DRD4 in Naganakidori, there is a deletion variant of one proline at the 24th residue in the repeat of nine prolines of exon 1. We thus conclude that artificial selection has operated on these different kinds of genetic variation in the DRD4 genes of Shamo and Naganakidori so strongly that the two domesticated varieties have differentiated to obtain their present opposite features in a relatively short period of time.